Centrifuge modelling on soft soil subjected to underwater vacuum preloading. Issue 3 (28th June 2019) - Hu, Liwen; Wang, Yongping; Liu, Zhijun
Abstract : The performance of soft soil subjected to underwater vacuum preloading was explored using geotechnical centrifuge model tests at different g -levels. A vacuum generator system was developed in a centrifuge to model the behaviour of underwater soft soil subjected to vacuum preloading. Sand drains were partially penetrated in soft soil. Vacuum gauges, pore-water pressure transducers and pressure transducers were used to measure the response of pressures and total stresses in the soil, while linear variable differential transformers and particle image velocimetry analysis techniques were employed to measure and analyse the deformation behaviour of underwater soft soil. Observations showed that the magnitude of reduction of pore-water pressure increased in the soil with an increase in water depth on the membrane. Meanwhile, on application of vacuum, the measured pore-water pressure below the membrane may be larger with an increase in the depth of water above the membrane due to a larger vacuum loss. Inward lateral displacement can be induced by underwater vacuum preloading to a limited extent in the treated and untreated zones. The lateral displacement in the treated zone may be negligible when the distance from the edge is larger than the thickness of clay.